The analysis group: diagnostic technique of organizational climate. Analysis of a case of alcoholism - Foradori, Horacio C. (Revista de Psicología, 1993)
The group-analysis technique, unlike other approaches such as the survey, studies the human group as a whole, which allows a considerable degree of depth regarding the essence and determination of the "symptoms" that the company presents, of the conflicts that occur within it. The group-analysis allows a vision of the company as a whole, in its daily life, in its work, in the relationships that individuals maintain, united by a common task that constitutes production.